2013
DOI: 10.3755/galaxea.15.101
|View full text |Cite
|
Sign up to set email alerts
|

FLUDI: Using digital images for measuring fish length

Abstract: Fish length is very important to the fishery research to identify fish population. In many fisheries, sample of fish length is a main parameter to identify fish reproduction, recruitment, growth and mortality. Currently in Malaysia, researchers have to measure the fish length one by one using measurement tools. This method is highly cost as we require buying fish first for measuring purposed. Moreover, manually measurement of fish length is time-consuming. Therefore, a method to measure the length of a fish au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…2010; Mustafa et al . 2013). The difference in accuracy could primarily be due to the differences in methodologies and algorithms used.…”
Section: Trends In Ciamentioning
confidence: 99%
See 1 more Smart Citation
“…2010; Mustafa et al . 2013). The difference in accuracy could primarily be due to the differences in methodologies and algorithms used.…”
Section: Trends In Ciamentioning
confidence: 99%
“…Interestingly, the use of CIA has shown a promising future in this aspect. Reports indicated that, the accuracy of measuring fish length by processing an underwater fish image ranges from 95% to 99.81% (Rahim et al 2010;Mustafa et al 2013). The difference in accuracy could primarily be due to the differences in methodologies and algorithms used.…”
Section: Trends In Ciamentioning
confidence: 99%
“…The result showed that this is the efficient method to sort fish online and can be applied widely in many fish farms. Mustafa et al [86] proposed this study to measure the length of fish automatically by image processing (FLUDI framework) instead of by measurement tools which are of high cost. Rastrelliger kanagurta and Selar crumenophthalmus species were used for this experiment.…”
Section: Measure Fish Sizementioning
confidence: 99%
“…However, the software can be applied to other objects without any object reference. The actual fish length from the digital image was tested by comparing the fish length obtained from the traditional measuring board (Figure 12) [86]. The result shows that the difference is very small, ranging from 0.74-2.19%.…”
Section: Measure Fish Sizementioning
confidence: 99%